OPTIMALISASI MANAJEMEN KURIKULUM DAN KESISWAAN UNTUK MENINGKATKAN MUTU LEMBAGA PENDIDIKAN ISLAM - Nailah Azzahra; Salsabila Cerah Lestari; Mulia Nursulaina Putri; Irdha Andini Joe; Rara Amelia (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aims to analyze the implementation of curriculum management and student management as strategies for improving the quality of Islamic educational institutions at MTs Al-Ihsan Pamulang. The research employed a qualitative approach using a case study method. Data were collected through observation, interviews, and documentation involving the principal, vice principals of curriculum and student affairs, teachers, and students as research informants. The findings indicate that curriculum management was implemented through the planning, implementation, and evaluation of learning based on the Merdeka Curriculum integrated with Islamic values. These strategies were supported by learning supervision, quality assurance, and the habituation of religious character in academic and non-academic activities. Meanwhile, student management was carried out through student admission processes, orientation activities, disciplinary guidance, extracurricular programs, and student evaluation. These activities contributed to character building, the development of students’ interests and talents, and the improvement of educational services. However, the implementation of both management systems still faced several obstacles, including limited use of learning technology, insufficient digital competence among teachers, declining interest from prospective students, and the absence of professional counseling teachers. This study concludes that the integration of curriculum and student management plays an important role in improving the quality of Islamic educational institutions both academically and in strengthening students’ character. ABSTRAK Penelitian ini bertujuan untuk menganalisis pelaksanaan manajemen kurikulum dan manajemen kesiswaan sebagai strategi peningkatan mutu lembaga pendidikan Islam di MTs Al-Ihsan Pamulang. Penelitian menggunakan pendekatan kualitatif dengan metode studi kasus. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi dengan melibatkan kepala madrasah, wakil kepala bidang kurikulum dan kesiswaan, guru, serta siswa sebagai informan penelitian. Hasil penelitian menunjukkan bahwa manajemen kurikulum dilaksanakan melalui perencanaan, pelaksanaan, dan evaluasi pembelajaran berbasis Kurikulum Merdeka yang diintegrasikan dengan nilai-nilai Islam. Strategi tersebut didukung oleh supervisi pembelajaran, penjaminan mutu, serta pembiasaan karakter religius dalam kegiatan akademik dan non-akademik. Sementara itu, manajemen kesiswaan dilakukan melalui pelaksanaan PPDB, orientasi siswa, pembinaan disiplin, kegiatan ekstrakurikuler, dan evaluasi peserta didik. Kegiatan tersebut berkontribusi dalam pembentukan karakter, pengembangan minat dan bakat, serta peningkatan kualitas layanan pendidikan. Namun, implementasi kedua manajemen tersebut masih menghadapi hambatan berupa keterbatasan pemanfaatan teknologi pembelajaran, kurang optimalnya kompetensi digital guru, penurunan minat peserta didik baru, serta belum tersedianya guru bimbingan dan konseling secara profesional. Penelitian ini menunjukkan bahwa keterpaduan manajemen kurikulum dan kesiswaan memiliki peran penting dalam mendukung peningkatan mutu lembaga pendidikan Islam secara akademik maupun karakter peserta didik.